Peran healthy lifestyle dan advertising intrusiveness terhadap repurchase intention mie instan Lemonilo - Ida Nur Fitriana; Mega Mirasaputri Cahyanti (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
This study aims to determine the importance of healthy lifestyle and advertising intrusiveness on repurchase intention of Lemonilo Instant Noodles. This study uses a quantitative method with a sample of 50 members of the Ikatan Cinta Community. Data analysis using Regression Analysis, classical assumption test, t test. The results of this research analysis state that each variable, namely healthy lifestyle and advertising intrusiveness, has a significant influence on repurchase intention. For marketers, this research is useful for improving marketing strategies by maintaining public trust in healthy products and improving the delivery of intrusive advertising. Further researchers can replace or add independent variables such as brand image, consumer perception, product quality or other variables or add dependent variables for example, consumer satisfaction, consumer loyalty or other variables and increase the number of respondents, question items covering a wider area.